Penerapan Teknologi Tepat untuk Produksi Eco-Paving guna Mewujudkan Lingkungan Hijau Desa Babakanlor Kecamatan Cikedal Kabupaten Pandeglang - Anggun Wahyu Dwi Astuti; Mohammad Husni; Ahmad Nur Muchlisin; Darin Shohwatul Islam; Wisnu Maulana (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The Eco-Paving-Based Plastic Waste Recycling Innovation Improvement Activity in Babakanlor Village, Cikedal District, Pandeglang Regency, is part of a community service program aimed at increasing local understanding of eco-paving innovations for recycling plastic waste, contributing to a green economy in the village. With the growing plastic waste issue, there is a need for environmentally friendly yet economically valuable management innovations. This program focuses on developing eco-paving-based plastic recycling in Babakanlor Village to promote a green economy at the village level. The method employed is participatory, involving the community through socialization, technical training, and evaluation of eco-paving results. Household plastic waste is processed into eco-friendly paving blocks through shredding, mixing with sand and oil, printing, and compaction. The resulting eco-paving products meet construction standards, reduce plastic waste, and create new business opportunities based on the circular economy. The program’s results indicate an increase in community skills, a reduction in plastic waste, and job creation within the village. Thus, eco-paving innovation based on plastic recycling is a strategic approach to overcoming environmental pollution and promoting a sustainable green economy in Babakanlor Village.